EFFORTS TO IMPROVE THE ABILITY TO READ AND WRITE THE QUR'AN WITH DEMONSTRATION METHOD - Maulidiyah, Adiba; Hakim, Lukman; Zaini, Ahmat; Nizar , Ahmat; Makhrus Ali, M. (International Journal of Multidisciplinary Reseach, 2025)
The ability to read and write the Qur'an is very important for every student at every level of education, especially at the Elementary School level which is the beginning of all levels of education. With good reading and writing skills, good learning outcomes will be achieved. However, the reading ability of third-grade students at Lambangkuning Elementary School is still low. The purpose of this study is to improve the ability to read and write the Qur'an by using a demonstration method for students. This type of research is classroom action research (CAR). The subjects were 17 third-grade students, covering planning, action, observation, and reflection. Data collection techniques used were observation and tests. Data analysis used was quantitative and qualitative. The results of the study showed an increase in the percentage of students' reading ability from cycle 1 to cycle 2. In cycle 1 it was only 46.9% and in cycle II it increased to 100% of students, said to have achieved the IDK determined by the researcher, namely 75%. This increase was achieved because the researcher made improvements to learning in the aspects of learning media, learning methods and learning models. In this study, the researchers used folio paper with letters, a demonstration method, and a cooperative learning model. Therefore, it can be concluded that the demonstration method, aided by folio paper with letters, improved the reading and writing skills of Lambangkuning Elementary School students.